A partial two sector banking model with interest on reserves. (24th August 2019) - Osell, Shawn
This paper develops a two-sector theoretical partial equilibrium model with interest on reserves (IOR) in the banking sector. It also constructs standard vector autoregression models with empirical data including IOR. The objective of this paper is to analyse the monetary policy transmission effects of the Federal Reserve's interest on reserve policy. Impulse response functions are applied to both the theoretical and empirical models. The estimated impulse response functions are then compared to the theoretical models impulse response functions in order to see how well the model fits the data. This paper's model finds that the interest on reserve tool and open market operations (OMO) have the same effect on the macroeconomy.